Physiological and transcriptome analysis elucidates the metabolic mechanism of versatile Porphyridium purpureum under nitrogen deprivation for exopolysaccharides accumulation - Ji, Liang; Li, Shaohua; Chen, Cheng; Jin, Haojie; Wu, Haizhen; Fan, Jianhua (Bioresources and bioprocessing, 2021)
Porphyridium purpureum is a mesophilic, unicellular red alga rich in phycoerythrin, sulfate polysaccharides, and polyunsaturated fatty acids. Nitrogen deficiency inhibited the growth of P. purpureum and resulted in yellowing of the cells and thickening of the extracellular viscousness sheath. Under nitrogen stress, the contents of total lipids and exopolysaccharides in P. purpureum were increased by 65.2% and 188.0%, respectively. We demonstrate that the immediate response of P. purpureum to nitrogen deficiency is mediated by carbon flow to polysaccharide synthesis, while the synthesis of lipids is enhanced as a permanent energy storage substance at the later stage. Based on transcriptome annotation information, we elucidate the synthesis pathway of polysaccharides from P. purpureum from the perspective of glycosyl-donor interconversion, and demonstrate that the n-6 pathway is the main synthesis pathway of polyunsaturated fatty acids. This study not only provides a production strategy for polysaccharides and fatty acids by single-celled marine red algae P. purpureum , but also provides targets for further genetic modification.